News about four Black-Figure Attic Cups attributed to the Lancastre Painter - Morais, Rui (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The study of a black-figure Attic cup belonging to a private Portuguese collection, generically framed in the FP Class (Flower-Palmette), and the identification of a parallel in the Staatliches Lindenau-Museum, in Altenburg, attributed to the same artist, led us to propose – in partnership with another author – a new painter whom we named as Lancastre Painter. In the study that we now present, we added two more black-figure cups that we think can be attributed to this painter – one is contemplated in the Beazley Archive, and was sold by the Bonhams auctioneer in the London market, and the other was included in the sales catalogue of the Royal-Athena Galleries in 1990. The study and presentation of these two last cups reinforces the aforementioned attribution and calls the attention to the possibility that we might come to identify other specimen attributed to the same painter.